Ecological impact of isolated cognitive relapses in MS. (January 2020) - Meli, Riccardo; Roccatagliata, Luca; Capello, Elisabetta; Bruschi, Nicolò; Uccelli, Antonio; Mancardi, Gianluigi; Inglese, Matilde; Pardini, Matteo
Isolated cognitive relapses (ICRs) are transient deficits in cognitive performance that are the only presentation of a multiple sclerosis (MS) relapse. Here, we evaluated the impact of ICRs on cognitive difficulties in daily activities (assessed with the Multiple Sclerosis Neuropsychological Screening Questionnaire, Informant Version (MSNQ-I)) to characterize ICRs' clinical relevance. We used 2-year-long retrospective data to compare 15 relapsing-remitting MS (RRMS) patients with ICRs with 57 RRMS patients presenting an asymptomatic gadolinium enhancing lesion (and no-ICRs). ICRs were associated not only with neuropsychological performance decline but also with an increase in the daily cognitive difficulties. These findings support the ecological relevance of ICRs.